A Meta-Regression Analysis to Evaluate the Effects of Narasin on Grow-Finish Pig Performance - Larissa L. Becker; Jordan T. Gebhardt; Mike D. Tokach; Jason C. Woodworth; Robert D. Goodband; Joel M. DeRouchey; Jenna A. Seltzer; Roger A. Arentson; Michael Shields; Christopher L. Puls (Kansas Agricultural Experiment Station Research Reports, 2023)
A meta-regression analysis was conducted to evaluate the effects of added narasin in growing-finishing pig diets to predict the influence on average daily gain (ADG), feed efficiency (G:F), and carcass yield. A database was developed containing 21 technical reports, abstracts, and refereed papers from 2012 to 2021 representing 35 observations for growth performance data in studies ranging from 35 to 116 days in length (overall data). In addition, within these 35 observations, individual period data were evaluated (143 observations) using weekly, bi-weekly, or monthly performance intervals (period data). Regression model equations were developed, and predictor variables were assessed with a stepwise manual forward selection procedure. Important variables in predicting the response to added narasin included ADG, average daily feed intake (ADFI), and G:F of the control pigs, feeding duration (shorter or longer than 65 days) and body weight (greater than or less than 230 lb). Using median values from the database for predictor variables, the meta-analysis indicated narasin would be expected to improve ADG between 1.06 to 1.65%, G:F between 0.71 to 1.71%, and carcass yield by 0.31% when fed for longer than 65 days.
Keywords: carcass yield; grow-finish pig; growth performance; ionophore; narasin